2021
DOI: 10.3390/ijms22179190
|View full text |Cite
|
Sign up to set email alerts
|

A Dansyl-Modified Sphingosine Kinase Inhibitor DPF-543 Enhanced De Novo Ceramide Generation

Abstract: Sphingosine-1-phosphate (S1P) synthesized by sphingosine kinase (SPHK) is a signaling molecule, involved in cell proliferation, growth, differentiation, and survival. Indeed, a sharp increase of S1P is linked to a pathological outcome with inflammation, cancer metastasis, or angiogenesis, etc. In this regard, SPHK/S1P axis regulation has been a specific issue in the anticancer strategy to turn accumulated sphingosine (SPN) into cytotoxic ceramides (Cers). For these purposes, there have been numerous chemicals … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…These differences could be explained by the very short half‐life of PF543 and the fact that SK1 is not inhibited during all the interval following each treatment. Molecular modifications have been applied to PF543 to improve its anticancer potential 63 or to extend its inhibitory capacity to additional sphingolipid enzymes 64 ; however, these new compounds were used at higher concentrations than the original drug, which could reduce specificity. The short half‐life of PF543 in mice raises the need to identify either new inhibitors or additional molecular modifications to increase PF543 stability in biological systems and improve its bioavailability in mouse models of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be explained by the very short half‐life of PF543 and the fact that SK1 is not inhibited during all the interval following each treatment. Molecular modifications have been applied to PF543 to improve its anticancer potential 63 or to extend its inhibitory capacity to additional sphingolipid enzymes 64 ; however, these new compounds were used at higher concentrations than the original drug, which could reduce specificity. The short half‐life of PF543 in mice raises the need to identify either new inhibitors or additional molecular modifications to increase PF543 stability in biological systems and improve its bioavailability in mouse models of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of the SPHK1 inhibitor PF-543 since it has been demonstrated that its dansylated form (DPF-543) provides high cytotoxicity. This compound also triggers aSMase activation, leading to a higher accumulation of ceramides within the cell ( 119 ). Other SPHK inhibitors, such as F-12509, SKI-I and FTY720 (Fingolimod), specifically inhibit SPHK1; ABC294640 (Opaganib) and K145 specifically inhibit SPHK2; and SKI-II which inhibits both SPHK1 and SPHK2.…”
Section: Discussionmentioning
confidence: 99%